Geology of the Yesilyurt gold deposit: an example of low-angle normal fault related mineralization, Eastern Anatolia-Turkey - Yildirim, Esra; Yildirim, Nail; Donmez, Cahit; Gunay, Kurtulus (Maden Tetkik ve Arama Genel Mudurlugu-Mta, 2021)
Yesilyurt gold mineralization is located within the provincial borders of Malatya and Adiyaman in the East Anatolian Region. This mineralization is one of the gold deposits which correlated with low-angle normal/detachment fault. Low-angle normal fault associated with a tectonic setting which is potential extensional in Paleogene-Neogene (?) term. Marble-recrystallized limestone which belongs to the metamorphic core is the dominant rock (footwall) type in the bottom plate of the fault zone. There are deformed graphitic calc-schists (hanging wall) in the upper plate of the fault zone. The fault zone is characterized by fault gauge, cataclasite, and breccia. While the cataclasite, and breccia are the principal ore host, there is weaker mineralization in fault gauge. Alteration assemblages are: (1) silica replacements/veinlets and, (2) quartz-pyrite replacements / veinlets. High gold contents are closely related to silicification and quartz-pyrite alteration which damaged the primary textures. Small volume syn-tectonic magmatic rocks are simultaneous and typically monitored in the silicified areas which are border on the high-grade gold mineralization. Mineralization is a non-base metalliferous Au depositthat contains Au/Ag similar to 1.07, As (similar to 0.27%), F (1.59%), and a trace amount of Sb. This deposit will lead to finding new gold deposits in Eastern Taurus Orogenic Belt.
Keywords: Yesilyurt gold mineralization; Detachment fault/Low-angle normal fault; Fault gauge; Cataclasite; Breccia